PARTISIPASI MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN (PBB) DI KELURAHAN TANGKERANG BARAT KECAMATAN MARPOYAN DAMAI KOTAPEKANBARU TAHUN 2013 - Saputra, Rizaldi; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Urban Village West Tangkerang Marpoyan District of Peace is one of the base land and building tax revenues in KotaPekanbaru that the collection process is assisted by the Village. In the execution of acceptance of Property Tax in the Village District of West Tangkerang Marpoyan Peaceful yet make a real contribution and not optimal. This study aims to determine the community's participation in the Property Tax On Tangkerang West Village District of Marpoyan Peace Pekanbaru City in 2013.The approach of this study used a qualitative approach, this type of research is a descriptive study. The focus of research is the effectiveness of participation, consisting of input, throughput, and output. Informants in this study is the Staff UPTD DPPKAD in revenues Office Pekanbaru, Secretary Tangkerang West Village District of Marpoyan Damai.Teknik data collection in this study using observations, interviews ,. Data analysis techniques used in this research is descriptive analysis techniques. The results showed, yet effective component inputs, while the throughput component can be said effective participation, and component outputs have not been effective. The factors inhibiting faced include lack fahamnya community to the importance of land and building tax in the financing of development, lack of concrete evidence of tax paid in improving public welfare, less gitanya authorities in collecting. Recommendations from the results of this study include increased motivation tax collector apparatus, the program on the importance of taxes to taxpayers, to collect data on the object and subject to service tax on taxpayers better and can achieve development goals.Keywords: Participation, Land and Building Tax, Effectiveness, Input, Throughput, Outpu